Enhancing the quality of fermented plant leaves: the role of metabolite signatures and associated fungi - Xing, Lei; Lei, Jinshan; Liu, Jie; Yang, Zhen; Chai, Zhishun; Cai, Wen; Zhang, Min; Meng, Delong; Wang, Yujie; Yin, Huaqun (Frontiers in Plant Science, 2024)
Fungi play a pivotal role in fermentation processes, influencing the breakdown and transformation of metabolites. However, studies focusing on the effects of fungal-metabolite correlations on leaf fermentation quality enhancement are limited. This study investigated specific metabolites and fungi associated with high and low-quality fermented plant leaves. Their changes were monitored over fermentation periods of 0, 8, 16, and 24 days. The results indicated that organoheterocyclic compounds, lipids, lipid-like molecules, organic nitrogen compounds, and phenylpropanoids and polyketides were predominant in high-quality samples. The fungi Saccharomyces (14.8%) and Thermoascus (4.6%) were predominantly found in these samples.These markers exhibited significant changes during the 24-day fermentation period. The critical influence of fungal community equilibrium was demonstrated by interspecies interactions (e.g., between Saccharomyces and Eurotium). A co-occurrence network analysis identified Saccharomyces as the primary contributor to high-quality samples. These markers collectively enhance the quality and sensory characteristics of the final product.